I am not able to get an answer for this problem. 8÷4[6-2(-8+3*2^3)] can you help?
I believe the solution provided by the above user is correct upto the 4th to the last line.
Use PEMDAS=> parentheses, exponential, multiplication, division, addition, subtraction (left to right)
After you have gotten the stuff within the brackets simplified upto [6-32] = [-26], the expression becomes,
8÷4[-26] (since we still have the bracket, we have to deal with it first)
= 8 ÷ (-104) (a÷b is same as a/b, eg. 4÷2 = 4/2 = 2)
= -1/13 (minus sign from -104 carries)